2015
DOI: 10.4238/2015.september.28.8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between single nucleotide polymorphisms in hypoxia-related genes and susceptibility to acute high-altitude pulmonary edema

et al.

Abstract: ABSTRACT. This study aimed to explore the relationship between genetic changes and high-altitude pulmonary edema (HAPE) susceptibility, and to screen for the key single nucleotide polymorphism (SNP) loci in the HAPE-susceptibility gene, by investigating the SNPs occurring in hypoxia-related genes in HAPE-susceptible and control (non-susceptible) populations. This research was conducted on Han recruits, who travelled to the Lhasa plateau (altitude, 3658 m). Ten loci located on ten genes extracted from the HAPE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Wu et al showed a correlation between single nucleotide polymorphisms in hypoxia-related genes like the PHD2 (SNPrs480902) and susceptibility to acute high-altitude pulmonary edema (HAPE). They found that the HAPE cases had a significant higher T-allele frequency than the control group [25]. Buroker et al described phenotypical differences between Han Chinese with acute mountain sickness (AMS) in the rs480902 SNP.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al showed a correlation between single nucleotide polymorphisms in hypoxia-related genes like the PHD2 (SNPrs480902) and susceptibility to acute high-altitude pulmonary edema (HAPE). They found that the HAPE cases had a significant higher T-allele frequency than the control group [25]. Buroker et al described phenotypical differences between Han Chinese with acute mountain sickness (AMS) in the rs480902 SNP.…”
Section: Discussionmentioning
confidence: 99%
“…People could be distinguished by significant individual variability in the expression levels of HIF and other HIF-dependent genes in leukocytes, which indicates phenotypic differences in its regulation. It was demonstrated that there is individual variability in the expression of HIF and its dependent genes in response to hypoxic or inflammatory stimuli, which, at least in part, is due to genetic polymorphisms [ 7 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Cellular Response To Hypoxic Exposurementioning
confidence: 99%
“…The exact mechanism underlying the development of HAPE remains unclear, although exaggerated pulmonary hypertension has been suggested to play a crucial important role . There’s a segment of the population affected individuals develop HAPE while exposed to high altitudes, probably due to individual variations and several genetic studies have demonstrated that a genetic susceptibility may play a role in the development of HAPE . The genetic susceptibility and the HAPE risk have been reported, including polymorphisms of the genes of NOS3, ACE, AGTR1, ADRB2, HLA, VEGF et al have been positively associated with HAPE.…”
Section: Introductionmentioning
confidence: 99%
“…5 There's a segment of the population affected individuals develop HAPE while exposed to high altitudes, probably due to individual variations and several genetic studies have demonstrated that a genetic susceptibility may play a role in the development of HAPE. 6,7 The genetic susceptibility and the HAPE risk have been reported, including polymorphisms of the genes of NOS3, 8 ACE, 9 AGTR1, 10 ADRB2, 11 HLA, 12 VEGF 13 At present, studies have been found that HAPE may have an important pathogenesis of inflammation. The roles of these cytokines in the development of HAPE are complicated.…”
Section: Introductionmentioning
confidence: 99%